Risk of depression and anxiety in 7.302 patients with sarcoidosis: a nationwide cohort study - Sikjær, Melina Gade; Hilberg, Ole; Farver-Vestergaard, Ingeborg; Ibsen, Rikke; Løkke, Anders (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: The aim was to investigate the association between sarcoidosis and anxiety and/or depression (A/D) in patients with sarcoidosis and comparators matched on age, gender, residency, and cohabitation status. Methods: Patients with newly diagnosed sarcoidosis between 2001 and 2015 were identified in the Danish National Patient Register. Cases were matched 1:4 with non-sarcoidosis comparators. We estimated the cumulative incidence of A/D using the Cumulative Incidence Function and the subdistribution hazard ratio (sHR) for A/D using the Fine-Gray subdistribution hazard model. Estimates were adjusted for socio-economic status and Deyo-Charlson Comorbidity Index. Results: We identified 7.302 cases and 26.145 matched comparators. The cumulative incidence of A/D after five years was 6.0% (95%CI 5.5-6.4) for cases and 4.2% (95%CI 4.0-4.4) for matched comparators. The cumulative incidence was higher among cases for both males and females and in all age-groups compared with the matched comparators. The adjusted-sHR for A/D was 1.38 (95%CI 1.24-1.53). The adjusted-sHR for A/D was 1.51 (95%CI 1.30-1.75) for male cases and 1.25 (95%CI 1.08-1.45) for female cases compared with the matched comparators. The adjusted-sHR for A/D was higher for cases in all age-groups compared with the matched comparators, although not statistically significant among cases aged 30-39 years (a-sHR 1.15; 95%CI 0.92-1.44). Conclusions: Sarcoidosis cases had a higher risk of A/D compared with matched comparators during 18 years of follow-up. The risk of developing A/D was greater for male and female cases and within all age-groups compared with the matched comparators.